Strukturalisme Levi-Strauss dalam Novel Sirkus Pohon - Liza Mawarni (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2021)
This study aims to reveal the deep structure of the Sirkus Pohon novel by Andrea Hirata which reflects the structure of the author's society. Using the Levi-Strauss structuralism approach, this qualitative descriptive research confirms nothing empirically visible but behind ideas. The main data of this study were obtained from the Sirkus Pohon novel written by Andrea Hirata, and the ethnographic data of the Belitung community as support. The analysis results show that there is a structure behind the novel that leads to the existence of pairs between one element and another. A connecting element bridges these two opposing elements, and the positional triangle or classification structure of forms three. This structure refers to the representation of the cultural structure of the author's society which is transformed into the socio-cultural phenomenon of the society, namely the religious phenomenon, which reflects the liminality of the Belitung Malay society. The structure of the Belitung Malay culture is unconsciously influences the way Belitung Malays think, act, and believe.